The Holdout Problem and Long-Term Contracting - Alexander Raskovich (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
The holdup problem of under-investment in specific capital has been studied extensively. Less attention has been paid to the "holdout" problem of over-investment in outside options. A buyer's gain from (unverifiably) developing an outside option exceeds the joint gain, given rent shifting when an inferior option binds in subsequent bargaining with the seller. Long-term contracts can solve holdout by increasing the buyer's surplus from trade within the relationship. With a nonbinding contract, however, the seller's participation constraint may require the buyer (who may be financially constrained) to pay a large signing bonus. This suggests a novel motive for vertical integration.
Keywords: 330